Holes in the safety net : federalism and poverty / edited by Ezra Rosser. - Rosser, Ezra (Cambridge University Press, 2019)
While the United States continues to recover from the 2008 Great Recession, the country still faces unprecedented inequality as increasing numbers of poor families struggle to get by with little assistance from the government. Holes in the Safety Net: Federalism and Poverty offers a grounded look at how states and the federal government provide assistance to poor people. With chapters covering everything from welfare reform to recent efforts by states to impose work requirements on Medicaid recipients, the book avoids unnecessary jargon and instead focuses on how programs operate in practice. This timely work should be read by anyone who cares about poverty, rising inequality, and the relationship between state, local, and federal levels of government.